Pengaruh Beban Kerja dan Kompensasi Terhadap Kinerja Karyawan PT Nico Jaya Pratama - Fahmi, Siti Nurfadhilah; Suherman, Enjang; Khalida, Laras Ratu (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The purpose of this research is to understand the effect of workload and compensation on employee performance either partially or simultaneously at PT Nico Jaya Pratama. A descriptive quantitative approach is applied in this study. The population involved in this study is all employees of PT Nico Jaya Pratama, especially 185 people who work in the E Assembly department plant. The simple random sampling method in the probability sampling technique is applied in selecting samples in this study. namely all employees of PT Nico Jaya Pratama with a random system. The Slovin formula with a level of 5% is used to collect samples of 127 employees. Employee Performance is the Dependent Variable, Workload is the Independent Variable, and Compensation is the Independent Variable. Using SPSS Statistic 26 software. Based on the results of the study, it was revealed that the workload is classified as high, with the highest value of 86.92 on the overload work task indicator. Compensation is classified as appropriate, with the highest TCR value of 86.92 on the insurance indicator. Performance is classified as good, with the highest TCR value of 86.92 on the ability to work together indicator. Workload directly plays a positive and significant role in the performance of PT Nico Jaya Pratama employees because it has a regression coefficient value of the workload variable (X1) which will increase employee performance (Y) by 0.632. Compensation directly has a positive and significant impact on employee performance at PT Nico Jaya Pratama because it has a regression coefficient of compensation variable (X2) which will increase employee performance (Y) by 0.415. Simultaneously, workload and compensation have a positive and significant impact on employee performance in the determination coefficient R2 of 0.899 proving that 89.9% of the variation in employee performance can be explained by workload and compensation.